Adaptations to frequent oocyte release in the ovary of the invasive snail Pomacea canaliculata (Caenogastropoda: Ampullariidae) - Winik, Beatriz Clara (2015)
The Ampullariidae (‘apple snails’) are freshwater caenogastropods of probable Gondwanan origin that are now indigenously distributed in tropical and temperate zones of southern North America, South America, Africa, India and South East Asia (Berthold, 1991). The family is a basal offshoot of the phylogenetic tree of the Caenogastropoda and comprises nine extant genera and c. 120 valid species (Hayes, Cowie & Thiengo, 2009), several of which are ecologically significant. In particular, Pomacea canaliculata (Lamarck, 1822) and P. maculata Perry, 1910 have invaded South East Asia (Halwart, 1994) and Spain (Oscoz, Tomás & Durán, 2010), where they have become serious pests of rice and other crops.